ECONOMICAL USE OF LAND AND WATER RESOURCES WITH THE OPTIONS. - Rakhimova Kizlarkhon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Land and water resources in all countries, and limited how much even if it seems like so little. Therefore, “the earth” and “water” in the form of may recommend in writing. Also measure land in Uzbekistan (447,97 thousand square kilometers). The earth of our more than 7% of the population living areas in part, we will use the way you burn and crop. The greater part of the rest of the water, the mountains, the desert, its, organizes steppe and steppe.